Perubahan Garis Pantai dan Pengaruhnya Terhadap Status Kepemilikan dan Penguasaan Tanah Timbul di Muara Sungai Wulan Tahun 1986-2016 - Condro, Hastuti Endang; Budi, Sanjoto Tjaturahono; Puji, Hardati (Geo-Image, 2018)
Change of the shoreline is an event that affected by the proceedings accretion and abrasion.Due to changes in the shoreline is the emergence of the terrestrial globe earth arising. Land arising is an asset valuable that can be used for the benefit of people in surrounding.The goals are 1 ) to identify a tendency change the shoreline years 1986-2016, 2 ) to identify speed change the shoreline, 3 ) to identify the causes of change the shoreline, and 4 ) to identify an impact the shoreline about the status of possession and tenure of land arising in the mouth of the Wulan river on 2016.Technique analysis the data used is a technique analysis interpretation imagery and descriptive analysis explorative.The result of this research are 1 ) the trend in the change the sea shore in Berahan Kulon village is accretion , while in Berahan Wetan village is abrasion , 2 ) the speed changes in land accretion is 29,4 m/year and on land abrasion 11,919 meters/year , 3 ) the process of accretion and abrasion caused by the difference in width of the river so as to affect material intake sediment that has come into the two rivers the sources of their astuaries , and 4 ) the status of ownership and mastery of fish-ponds within Berahan Kulon village is 98 % sppt and 2 % have a certificate and the status majority of personally.